A comparative study of endogenous phospholipase A2 inhibitors in the serum of Brazilian pit vipers. (15th July 2022) - Kavazoi, Victor Koiti; Serino-Silva, Caroline; Bittencourt Rodrigues, Caroline Fabri; Hatakeyama, Daniela Miki; Carvalho de Souza, Daniel; Grego, Kathleen Fernandes; de Morais-Zani, Karen; Tanaka-Azevedo, Anita Mitico
Abstract: This work compared the presence of phospholipase A2 inhibitors (PLIs) in the serum of 19 snake species maintained at Instituto Butantan to better understand the mechanisms of venom resistance in snakes and improve the treatment of snakebite. PLI was isolated from blood of 19 snake species by one-step chromatography and identified in all samples, besides its identity was confirmed through the interaction with both phospholipase A2 and anti-γPLI. These findings highlight the diversity of snake serum PLIs and emphasize the importance of structure-function studies. Graphical abstract: Image 1 Highlights: Isolation and characterization of the PLIs in 8 new Bothrops snake species. PLIs showed only one or two bands of 25 kDa monomers in all Bothrops, Crotalus and Boa, differing to N. kaouthia pattern. Variable numbers of the spots in 2D electrophoresis suggested a variable isoform composition of the PLIs in snake blood. The immunoreactivity assays confirmed the proteins as PLIs, evidencing the interaction with the PLA2 from C. d. terrificus.